Avaliação institucional externa em um centro municipal de educação infantil de Osasco-SP - Santos, Maria Aparecida Mendes dos (2022)
The research that is outlined here started from our own concerns as a teacher of Early Childhood Education in the Municipality of Osasco. The investigation is complete. The research topic was “The External Institutional Evaluation of a Municipal Center for Early Childhood Education in the Municipality of Osasco”, considering that the selected school underwent an annual external evaluation that did not seem to be well understood by the school community. Our initial observations also showed that the school needed to undergo some changes in several aspects: structural; material; didactic-pedagogical resources; of the communicative relationships between the different segments of the school and, mainly, in the aspect of information management of the results of these external evaluations. In view of these observations, we started from the hypothesis that the way in which the External Institutional Assessment process, carried out in the studied school, was carried out, hindered the transformation of school practices and the perception of school actors about the improvements obtained from it. From this perspective, we sought to understand the meaning of Institutional Assessment carried out in the researched school, for which some questions were raised: a) How are External Institutional Assessments developed in the studied school? b) What are the results analysis procedures and how is the External Institutional Assessment feedback given in this school? c) Is there collective discussion and effective participation of the actors involved in the process of School Management actions? Seeking answers to such questions, we first carried out the documentary research and analysis of the Political- Pedagogical Project and the results of the external institutional evaluation of the years 2018 and 2019. This investigation had the general objective of understanding how the external institutional evaluation has contributed to the improvement of the school as a whole. This is qualitative research and the methodology used includes document analysis and questionnaires carried out remotely using Google forms. The subjects of this investigation are two-day care teachers, two managers, two support workers and two mothers representing the families. The theoretical contribution is based on research on the subject addressed based on the Quality Indicators in Early Childhood Education (IQEI), on the work of Heloisa Lück and on official documents from the municipality of Osasco, namely: the Institutional Assessments of 2018 and 2019, Political Pedagogical Project of the school and legal regulations that deal with Institutional Assessment. The results allowed us to verify that all schools in the municipality are evaluated by the “Rede Primavera” (fictitious name) in the same way, and, annually, they undergo this external evaluation. We understand that external assessments can become productive if they are associated with a collective and participatory process of institutional self-assessment. The school should promote its self- assessment based on the assumptions of dialogical assessment, in an educational- communicative context that allows for collective, dialogical, reflective, critical and awareness-raising discussion of the results. Only the collective of the school united in discussion and knowing its potentialities and, mainly, its weaknesses can transform it.